(a+2)(a+1)=

Simple and best practice solution for (a+2)(a+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+2)(a+1)= equation:


Simplifying
(a + 2)(a + 1) = 0

Reorder the terms:
(2 + a)(a + 1) = 0

Reorder the terms:
(2 + a)(1 + a) = 0

Multiply (2 + a) * (1 + a)
(2(1 + a) + a(1 + a)) = 0
((1 * 2 + a * 2) + a(1 + a)) = 0
((2 + 2a) + a(1 + a)) = 0
(2 + 2a + (1 * a + a * a)) = 0
(2 + 2a + (1a + a2)) = 0

Combine like terms: 2a + 1a = 3a
(2 + 3a + a2) = 0

Solving
2 + 3a + a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(2 + a)(1 + a) = 0

Subproblem 1

Set the factor '(2 + a)' equal to zero and attempt to solve: Simplifying 2 + a = 0 Solving 2 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + a = 0 + -2 a = 0 + -2 Combine like terms: 0 + -2 = -2 a = -2 Simplifying a = -2

Subproblem 2

Set the factor '(1 + a)' equal to zero and attempt to solve: Simplifying 1 + a = 0 Solving 1 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + a = 0 + -1 a = 0 + -1 Combine like terms: 0 + -1 = -1 a = -1 Simplifying a = -1

Solution

a = {-2, -1}

See similar equations:

| (r-7)(3r^2-7r+5)=0 | | m^3-1=0 | | 5400=x(180-1.5x) | | -7n+8=-3n-16 | | 0.65x+0.05(2-x)=0.10(-47) | | (7x-3)(4x^2-6x+4)=0 | | -x^2-3x-4=0 | | 2x-1=70 | | -3=3x-13 | | 7/6x=120 | | 2x-8=180/3 | | 70=x-13 | | x-13=70 | | 0.20x+0.05(12-x)=0.10(0) | | 6x+7=5x+8 | | (1−x)^(1/3)−0.11−1/3x | | 36-(18-x)+(18-x)= | | 2x+4+4x-4=180 | | x^3+50x+625=0 | | (6m-1)(m^2-7m-1)=0 | | 6x+2x+10=90 | | Y=1/2(12) | | -4.9t^2+15t+100=0 | | 8X+6=40 | | 3x-1=16/2 | | (49x^4)1/2 | | 90+50+x=180 | | (-2/1/7)p=-3 | | 6+78=39x+9 | | 5x-8x-3x+7x^2= | | 7(12-2x)=4(3-3x) | | -2.4p=-7.2 |

Equations solver categories